The President's Weekly Address - Obama, Barack H (Daily Compilation of Presidential Documents, 2010)
It's not just the medal count that's inspiring, though we've certainly done great on that score. What's truly inspiring is the character of the men and women who have won those medals, the sacrifices they've made, the integrity they've shown, the indomitable Olympic spirit that says no matter who you are or where you come from or what difficulties you may face, you can work hard and train hard and still triumph in the end. That's why we watch.